Curriculum spaces for connecting to children's multiple mathematical knowledge bases. Issue 4 (4th July 2019) - Land, Tonia J.; Bartell, Tonya G.; Drake, Corey; Foote, Mary Q.; Roth McDuffie, Amy; Turner, Erin E.; Aguirre, Julia M.
Abstract: Elementary mathematics curriculum materials can serve as a lever for instructional change. In this paper, we promote a particular kind of instructional change: supporting teachers in learning to integrate children's multiple mathematical knowledge bases (MMKB), including children's mathematical thinking and children's home and community-based mathematical funds of knowledge, in instruction. A powerful means of supporting pre-service teachers in integrating children's MMKB in instruction may be to scaffold teachers' noticing of potential spaces in elementary mathematics curriculum materials for connecting to children's MMKB and then developing practices for leveraging these spaces during instruction. We focus on existing and potential spaces in written curriculum materials, or curriculum spaces, so as to better support teachers in enacting curriculum that opens spaces for connecting to children's MMKB.